ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI KAB/KOTA SUMATERA BARAT - Afyana Afdal; Mike Triani (Jurnal Ecogen, 2018)
the government in the economic sector towards economic growth in West Sumatra. This type of research is descriptive and associative, namely research that describes research variables and finds the presence or absence of the influence of variables with independent variables. Data type is secondary data (Pool Time Series). The data writing technique in this research is literature study and documentation from 2012 to 2016. Descriptive and inductive data analysis are: Classical Assumption Test (Heteroscedasticity Test), Panel Regression Model, T Test and F Test.The results of this study conclude that a significant workload on economic growth in West Sumatra, one of the factors that influence economic growth in West Sumatra, and also the sector economy does not significantly influence poverty in West Sumatra. In connection with the results of the study, the suggestions needed are important to improve the quality, quality of employment opportunities, in order to reduce poverty and improve the economy in West Sumatra. Keywords: Job Opportunities, Poverty, Government Expenditures, Economic Growth